2019
DOI: 10.2147/ndt.s222567
|View full text |Cite
|
Sign up to set email alerts
|

<p>Co-Occurring Psychiatric and Substance Use Disorders: Clinical Survey Among a Rural Cohort of Italian Patients</p>

Abstract: PurposeDual diagnosis (DD) is the co-occurrence of both a mental illness and a substance use disorder (SUD). Lots of studies have analysed the integrated clinical approach, which involves both psychiatry and toxicology medical experts. The purpose of this study is to analyse the socio-demographic characteristics and treatment strategies of patients with DD in a rural area of Italy.Patients and MethodsClinical data of 750 patients were collected in 2016 through the analysis of health plan records.ResultsThe rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
(31 reference statements)
1
3
0
Order By: Relevance
“…28 Moreover, a high prevalence of comorbid AUD/SUD among schizophrenic and psychotic patients, with a rate of comorbidity assessed between 40% and 70%, is internationally recognized worldwide. 29,30 Specifically, the recorded prevalence of SUD is 25.1% in patients with schizophrenia and 20.1% in those with bipolar disorder, 31 confirming recent trends and sociocultural changes, and evidence from the recent pandemic period. In Italy there are no recent and systematic epidemiological data regarding the rate of co-occurring disorders among people with SUD patients; a recent Italian study conducted in a rural area of Liguria Region has shown that patients with a psychiatric diagnosis and a SUD/AUD in drug abuse services are 24%.…”
Section: Dovepresssupporting
confidence: 52%
“…28 Moreover, a high prevalence of comorbid AUD/SUD among schizophrenic and psychotic patients, with a rate of comorbidity assessed between 40% and 70%, is internationally recognized worldwide. 29,30 Specifically, the recorded prevalence of SUD is 25.1% in patients with schizophrenia and 20.1% in those with bipolar disorder, 31 confirming recent trends and sociocultural changes, and evidence from the recent pandemic period. In Italy there are no recent and systematic epidemiological data regarding the rate of co-occurring disorders among people with SUD patients; a recent Italian study conducted in a rural area of Liguria Region has shown that patients with a psychiatric diagnosis and a SUD/AUD in drug abuse services are 24%.…”
Section: Dovepresssupporting
confidence: 52%
“…An Italian study in rural users found psychiatric comorbidities with SUD as – mood disorders (72%) > personality disorders (60%) > psychotic disorders (24%) > cognitive disorders (17%) > anxiety disorders (7%). [ 14 ] Bhat et al . [ 51 ] īn a study from Kashmir, India found that 62.2% patients with opioid use and another psychiatric illness were from a rural background, most commonly ADHD (24.3%) > depressive disorder (10.8%) > panic disorder (4.1%) > OCD and personality disorders (1.4%).…”
Section: Discussionmentioning
confidence: 99%
“…Fewer social risk factors and stigmatization among rural patients were factors sighted. [ 6 13 14 ] Underpinnings of these differences are speculative. Although urban living is associated with more stress, breakdown of support systems, and economic instability; lack of availability, accessibility, and affordability of mental health services in rural areas still remain important.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the majority (42.8%) of these individuals were dependent on central nervous system depressants such as heroin and cannabis. On the other hand, the most common mental illnesses identified were mood disorders (40%), personality disorders (33.3%), and schizophrenia or other psychotic disorders (13.3%) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%